Research Progress on Oxygen Reduction Catalyst Materials for Proton Exchange Membrane Fuel Cells - Cao Beiheng (E3S Web of Conferences)
The sustainable development of society gives rise to the increasing energy demand, making environmental pollution a problem that cannot be ignored. Among them, fuel cells are attracting attention as efficient and environmentally friendly. Proton exchange membrane fuel cells (PEMFCs) represent an advanced and eco-friendly energy conversion technology with substantial potential in transportation, distributed power generation, and other applications, while their performance can be remarkably impeded by the cathodic oxygen reduction reaction (ORR) which exhibits slow kinetics. Pt-based catalysts are the preferred materials for catalysis but are detrimental to the practical application of fuel cells due to their high cost and instability. Therefore, it is essential to develop stable and low-cost cathode catalysts. This paper reviews the advancements in cathode catalysts for PEMFCs, encompassing traditional platinum-based catalysts and their enhancement strategies, as well as the current status of emerging non-platinum-based catalysts. The paper also outlines future research directions for these cathode catalysts.